Exploring the Process of Digital Storytelling in Mental Health Research: A Process Evaluation of Consumer and Clinician Experiences. Issue 1 (11th September 2017) - De Vecchi, Nadia; Kenny, Amanda; Dickson-Swift, Virginia; Kidd, Susan
Digital storytelling is an art-based research method that has potential to engage mental health consumers and clinicians in dialogue about their lived experiences. However, few studies have examined the process of digital storytelling and people's perspectives about making digital stories. In this article, a process evaluation framework is used to explore two digital storytelling workshops conducted with mental health consumers and clinicians. Project planning and implementation documents were collated, and interviews conducted with workshop participants thematically analyzed. Data were combined with facilitator reflections and are reported using a process evaluation framework. Findings indicate that the digital storytelling process is a useful research method that can be used to create a space where power differentials between consumers and clinicians are made visible and shared dialogue can develop. Recommendations from the study include the importance of employing skilled consumer and clinician support personnel to guide the process of participation and negotiate ethical tensions to ensure participant safety.